Instalação de microgeração distribuída com fonte fotovoltaica nas estações de telecomunicações - Rodrigues, Mauro Fonseca (2013)
This dissertation presents the feasibility study for integration of microgeneration of electricity with photovoltaic power in telecommunications stations. From the Resolution 482/2012 of ANEEL, April 2012, microgeneration (installed capacity equal to or less than 100 kW) began to have the capacity considered in the reckoning power of the Brazilian electric system. As the Brazilian telecommunications system is present in all locations with more than 100 residents there is the possibility of creating a network of distributed micro generation, using the similarities between these two systems, telecommunications and power generation using photovoltaic source. For this, there is a need to analyze the generation capacity in contrast to the electricity consumption of the telecommunications stations. After, was carried out the application of concepts of Economic Engineering and Simplex Method of Linear Programming to evaluate the proposed system on the financial feasibility, considering the energy saving and some scenarios sale of energy used for the distribution system of electric power of the local concessionaire. From these analyzes was made possible to verify that the system proved to be attractive both for its assessment of Engineering Economy, as the Simplex Method, proving that its application can bring benefits to telecommunications companies and distribution network that will have less load to cater. However, the sale of energy from microgeneration this may decrease the reliability of the telecommunications system and therefore is not recommended.